Selection on plant traits in hedgerow ground vegetation: The effect of time since conversion from conventional to organic farming - Damgaard, Christian; Strandberg, Beate; Strandberg, Morten; Aude, Erik; Sørensen, Peter Borgen; Nielsen, Knud Erik; Bruus, Marianne (Basic and applied ecology, 2014)
This paper aims at characterizing the response of hedgerow ground flora to conversion of the surrounding fields from conventional farming to an organic farming practice. The effect of time since conversion from conventional to organic farming on the neighbouring hedgerow vegetation was examined by measuring selection on plant species and plant traits in the ground flora of 57 hedgerows adjacent to agricultural fields subject to organic or conventional management. Species richness increased significantly with time since conversion to organic farming until a maximum was reached. There were significant changes in community weighted average trait value in seven out of fifteen plant traits, and in functional diversity in two out of three groups of traits. In contrast to hypotheses, transition to organic farming generally selected for plant species that are less adapted to competing for light, whereas there were no effects on life form and lifespan. When all plant traits were analyzed together in a regression tree analysis, 31% of the variance was explained by five plant traits in the pruned tree, indicating that factors other than farming practice have a large influence on hedgerow ground flora. Das Ziel dieser Untersuchung ist es, die Reaktion der Bodenflora in Hecken auf die Umstellung von benachbarten Feldern von konventioneller auf biologische Bewirtschaftung zu beschreiben. Der Effekt der Zeit seit Umstellung auf die Vegetation der benachbarten Hecken wurde untersucht, indem die Selektion auf Pflanzenarten und Pflanzenmerkmale gemessen wurde. Der Artenreichtum stieg signifikant mit der Zeit seit Umstellung auf biologische Bewirtschaftung bis ein Maximum erreicht war. Es gab signifikante Änderungen des gewichteten mittleren Merkmalswertes der Gemeinschaften bei sieben von fünf-zehn Merkmalen und der funktionellen Diversität bei zwei von drei Merkmalsgruppen. Im Gegensatz zu unseren Hypothesen erfolgte durch die Umstellung auf biologische Bewirtschaftung generell eine Auslese von Pflanzenarten, die weniger gut an die Konkurrenz um Licht angepasst sind, während es keine Auswirkungen auf Lebensform und Lebensdauer gab. Bei der gemeinsamen Analyse aller Pflanzenmerkmale in einem Regressionsbaum mit Pruning wurden 31% der Varianz durch fünf Merkmale erklärt. Dies zeigt an, dass andere Faktoren als die Bewirtschaftungsweise einen starken Einfluss auf die Bodenflora der Hecken haben.